Decidual macrophages and Hofbauer cells in fetal growth restriction - Bezemer, Romy Elisa; Faas, Marijke M.; van Goor, Harry; Gordijn, Sanne Jehanne; Prins, Jelmer R. (Frontiers in Immunology, 2024)
Placental macrophages, which include maternal decidual macrophages and fetal Hofbauer cells, display a high degree of phenotypical and functional plasticity. This provides these macrophages with a key role in immunologically driven events in pregnancy like host defense, establishing and maintaining maternal-fetal tolerance. Moreover, placental macrophages have an important role in placental development, including implantation of the conceptus and remodeling of the intrauterine vasculature. To facilitate these processes, it is crucial that placental macrophages adapt accordingly to the needs of each phase of pregnancy. Dysregulated functionalities of placental macrophages are related to placental malfunctioning and have been associated with several adverse pregnancy outcomes. Although fetal growth restriction is specifically associated with placental insufficiency, knowledge on the role of macrophages in fetal growth restriction remains limited. This review provides an overview of the distinct functionalities of decidual macrophages and Hofbauer cells in each trimester of a healthy pregnancy and aims to elucidate the mechanisms by which placental macrophages could be involved in the pathogenesis of fetal growth restriction. Additionally, potential immune targeted therapies for fetal growth restriction are discussed.